Biomass CO2 gasification with CaO looping for syngas production in a fixed-bed reactor. (April 2021) - Gao, Ningbo; Śliz, Maciej; Quan, Cui; Bieniek, Artur; Magdziarz, Aneta
Abstract: The most important challenge in solid feedstock thermal conversion methods is minimising CO2 emissions. In this work, the gasification of pine sawdust in a mixture of N2 and CO2 was investigated for the reduction of CO2 by a calcium oxide loop. The experiments were conducted at 600, 700, and 800 °C in a fixed-bed reactor. The biomass was mixed with the calcium oxide at a ratio of 1:1. The chemical composition of the syngas was analysed using gas chromatography. Moreover, the high heating values of the received gas samples were calculated, and thermogravimetric analysis and Fourier-transform infrared spectroscopy analysis were performed to investigate the absorption of CO2 by CaO. The results of the gasification process showed that the syngas contained CO, CH4, CO2, H2, N2, and other low hydrocarbons. The most significant results were obtained for a 2:1 ratio of N2 to CO2 at 700 °C, and a CO2 reduction of 25% was observed. Moreover, the catalytic properties of CaO increased the concentration of H2 in the produced syngas by up to 10%. A temperature of 800 °C was too high for the carbonation reaction of CaO. This study presents a possible solution for achieving negative carbon emissions. Highlights: Gasification in CO2 atmosphere of biomass mixed with CaO was conducted. Influence of temperature and CO2 concentration on produced gas was studied. An addition of CaO to a biomass feedstock decreased CO2 emission by 58.7%. TG, FTIR and gas chromatography were used to investigate CO2 absorption. Negative carbon emission was achieved with calorific value of gas up to 19.74 MJ/m 3 .